Factors associed with rist for STD/AIDS among students in the nursing course at the Federal University of Mato Grosso – Sinop Campus. - Gatto, V.; Oliveira, R. R.; Flores, C. A. S. (Scientific Electronic Archives, 2018)
Abstract. The sexuality is present in every human being’s life is it searches for confirmation during, when the individual goes through a loto f transformation. Regarding sexuality adolescence is a time when the Young lives new experiences being exposed to risks such as acquiring STD/AIDS. So the present study hás performed a study of the students’sexual profile in the first and last semester of nursing course at the Federal University of Mato Grosso, and as well as identifying and companing the factors associated with risk of infection by the STD/AIDS presented by these students. Data collection occured through objective questionnaire composed of fifteen questions approaching data related to sexual behavior, knowledge about STD/AIDS, perceptions of risk to these diseases and the use of alcoholic beverages and ilicit drugs before sexual intercourse. It has been observed that both students from yhe first and mainly students from the last semester are exposed the risk of getting STD/AIDS, among them the high number of sexual partners non-regular condom use during sex stand out, there hás been a perception of invulnerability against these diseases and the use of alcoholic beverages before sexual intercourse. So it’s evident the need to implement strategies to reduce these risk factors and having a greater awareness of students about at theme.